2022
DOI: 10.1002/cnm.3585
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical response of human rib cage to cardiopulmonary resuscitation maneuvers: Effects of the compression location

Abstract: The biomechanical response of a human rib cage to cardiopulmonary resuscitation maneuvers was investigated by means of finite element simulations. We analyzed the effect of the location where the force was applied on the achieved compression depths and stress levels experienced by the breastbone and ribs. For compression locations on the breastbone, a caudal shift of the application area toward the breastbone tip resulted in a 17% reduction of the force required to achieve a target 5 cm compression depth. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 65 publications
(131 reference statements)
0
17
0
Order By: Relevance
“…In the present study, we assume a CS value of 1.5 for the costal cartilages, which leads to E c = 27 MPa according to Forman's formula. Suazo et al 15 showed that using this E c value, together with a Poisson ratio of η c = 0.45 for the cartilage, the linear elastic model reproduced fairly well the experimental test results of Forman and Kent 22 …”
Section: Models and Methodsmentioning
confidence: 59%
See 4 more Smart Citations
“…In the present study, we assume a CS value of 1.5 for the costal cartilages, which leads to E c = 27 MPa according to Forman's formula. Suazo et al 15 showed that using this E c value, together with a Poisson ratio of η c = 0.45 for the cartilage, the linear elastic model reproduced fairly well the experimental test results of Forman and Kent 22 …”
Section: Models and Methodsmentioning
confidence: 59%
“…In the present study, the parameters used in the elastoplastic model for the bone tissue are E b = 7 GPa, η b = 0.45, σ Y = 30 MPa and E T = 2 GPa. Suazo et al 15 showed that these parameter values produced good simulations of the rib bending experiments previously reported by Kindig et al 29 …”
Section: Models and Methodsmentioning
confidence: 64%
See 3 more Smart Citations